Biết số tự nhiên (n) thỏa mãn (C_n^1 + 2dfrac((C_n^2))((C_n^1)) + ... + ndfrac((C_n^n))((C_n^(n - 1))) = 45). Tính (C_(n + 4)^n?)

Lưu lại

Biết số tự nhiên $n$ thỏa mãn $C_n^1 + 2\dfrac{{C_n^2}}{{C_n^1}} + ... + n\dfrac{{C_n^n}}{{C_n^{n - 1}}} = 45$. Tính $C_{n + 4}^n?$

Đáp án: A

Xét SHTQ:

$\begin{array}{l}k\dfrac{{C_n^k}}{{C_n^{k - 1}}}\\ = k.\dfrac{{n!}}{{k!\left( {n - k} \right)!}}.\dfrac{{\left( {k - 1} \right)!\left( {n - k + 1} \right)!}}{{n!}}\\ = k.\dfrac{{n - k + 1}}{k} = n - k + 1\end{array}$

Khi đó ta có:  

      $C_n^1 + 2\dfrac{{C_n^2}}{{C_n^1}} + ... + n\dfrac{{C_n^n}}{{C_n^{n - 1}}} = 45$

$\begin{array}{l} \Leftrightarrow n + \left( {n - 1} \right) + \left( {n - 2} \right)\\ + ... + \left( {n - \left( {n - 1} \right)} \right) = 45\\ \Leftrightarrow n.n - \left( {1 + 2 + 3 + ... + n - 1} \right)\\ = 45\\ \Leftrightarrow {n^2} - \dfrac{{n\left( {n - 1} \right)}}{2} = 45\\ \Leftrightarrow 2{n^2} - {n^2} + n = 90\\ \Leftrightarrow n = 9\end{array}$

Khi đó $C_{n + 4}^n = C_{13}^9 = 715$

Chọn A.

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên